Enhanced symmetrical split ring resonator for metallic surface crack detection - Rammah A. Alahnomi; Z. Zakaria; Zulkalnain Mohd Yussof; Tole Sutikno; Ammar Alhegazi; Ahmed Ismail Abu-Khadrah (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
An enhanced sensor based on symmetrical split ring resonator (SSRR) functioning at microwave frequencies has been proposed in order to detect and characterize the metal crack of the materials. This sensor is based on perturbation theory, in which the dielectric properties of the material affect the quality factor and resonance frequency of the microwave resonator. Conventionally, coaxial cavity, waveguide, dielectric resonator techniques have been used for characterizing materials. However, these techniques are often large, and expensive to build, which restricts their use in many important applications. Thus, the enhanced bio-sensing technique presents advantages such as high measurement sensitivity with the capability of suppressing undesired harmonic spurious and permits potentially metal crack material detection. Hence, using a High Frequency Structure Simulator (HFSS) software, the enhanced sensor is modeled and the reflection S11 is performed for testing the aluminum metal with crack and without crack at the frequency range of 100 MHz to 3GHz. Variation of crack width and depth has been investigated and the most obvious finding emerged from this study is that the ability of detecting a minimum of sub-millimeter crack width and depth which is a round 10 ????m width or depth where the minimum shift of reflected frequency is recorded at 6.2 MHz and 3 MHz for crack width and depth respectively. The enhanced SSRR provides high capability of detecting small crack defection by utilizing the interaction between coupled gap resonators and it is useful for various applications such as aircraft fuselages, nuclear power plant steam generator tubing, and steel bridges and for others that can be compromised by metal fatigue.